State and Regional Financial Development Planning Mechanism - Darwin H. L Tobing; Zubakhrum Tjenreng (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the mechanism of national and regional financial development planning within Indonesia’s decentralized governance system. Employing a qualitative approach, the analysis is grounded in the concept of development planning as a structured and anticipatory process, public policy as a deliberate governmental intervention, and fiscal theory as institutionalized rights and obligations. The findings reveal suboptimal integration of planning and budgeting frameworks—RPJMN, RPJMD, RKP, and RKPD—resulting in fragmented policy execution and fiscal inefficiencies. Implementation challenges include limited technocratic capacity in regional planning bodies (Bappeda), politicization of development priorities, and weak deliberative effectiveness of Musrenbang forums. Digital systems such as SIPD and KRISNA remain underutilized due to technical and human resource constraints. To address these gaps, the study advocates for performance- and data-based planning reforms, fiscal alignment between central and local governments, and institutional strengthening toward adaptive and accountable governance. The study highlights the imperative for coherent policy and fiscal instruments to realize inclusive, competitive, and results-oriented national development aligned with the Vision of Golden Indonesia 2045.